Gir and Guzerat cow milk production and composition according to lactation stage, somatic cell count, physiological state and body condition - Thalita Polyana Monteiro Araújo; Adriano Henrique do Nascimento Rangel; Guilherme Ferreira da Costa Lima; Maria Gabriela Campolina Diniz Peixoto; Stela Antas Urbano; Joadilza da Silva Bezerra (Acta Scientiarum. Animal Sciences, 2018)
This work was realized to evaluate lactation stage, physiological state, somatic cell count (SCC) and body condition score (BCS) on production and composition of cow's milk from Gir and Guzerat breeds were studied. Ninety-eight cows were analyzed and classified according to their physiological state, lactation stage, SCC and BCS. Milk production was weighed monthly to obtain production data. Composed samples were collected in vials containing preservatives and sent to the laboratory for analysis. Data were used for statistic descriptive analysis and analysis of variance. Higher milk production in the first 60 days of lactation was observed. Fat, protein and total solids concentration increased according to the increase of days in milk; while lactose concentration decreased. Higher levels of fat, protein and total solids in milk of non-pregnant cows were observed; while pregnant cows had higher daily production and higher lactose content in their milk. Higher lactose levels in milk were observed in animals with lower SCC. The BCS had no effect on milk composition or on somatic cell count. Zebu cow milk production and composition are influenced by lactation stage, physiological state and SCC.